Anticancer potential of a photoactivated transplatin derivative containing the methylazaindole ligand mediated by ROS generation and DNA cleavage. Issue 33 (11th July 2016) - Pracharova, Jitka; Radosova Muchova, Tereza; Dvorak Tomastikova, Eva; Intini, Francesco P.; Pacifico, Concetta; Natile, Giovanni; Kasparkova, Jana; Brabec, Viktor
Abstract : Photoinduced DNA damage by trans -[PtCl2 (NH3 )(1-methyl-7-azaindole)] is related to its photocytotoxic activity. Abstract : The limitations associated with the clinical utility of conventional platinum anticancer drugs have stimulated research leading to the design of new metallodrugs with improved pharmacological properties, particularly with increased selectivity for cancer cells. Very recent research has demonstrated that photoactivation or photopotentiation of platinum drugs can be one of the promising approaches to tackle this challenge. This is so because the application of irradiation can be targeted exclusively to the tumor tissue so that the resulting effects could be much more selective and targeted to the tumor. We show in this work that the presence of 1-methyl-7-azaindole in trans -[PtCl2 (NH3 )(L)] (L = 1-methyl-7-azaindole, compound1 ) markedly potentiated the DNA binding ability of1 when irradiated by UVA light in a cell-free medium. Concomitantly, the formation of cytotoxic bifunctional cross-links was markedly enhanced. In addition, 1, when irradiated with UVA, was able to effectively cleave the DNA backbone also in living cells. The incorporation of 1-methyl-7-azaindole moiety had also a profound effect on the photophysical properties of1, which can generate singlet oxygen responsible for the DNA cleavage reaction. Finally, we found that1, upon irradiation with UVA light, exhibited a pronounced dose-dependent decrease in viability of A2780 cells whereas it was markedly less cytotoxic if the cells were treated in the absence of light. Hence, it is possible to conclude that1 is amenable to photodynamic therapy.